Venus fly traps and waterwheels : spring traps of the plant world - Gentle, Victor (Milwaukee, Wis. : Gareth Stevens Publishing, 1996)
This book describes the physical characteristics of these carnivorous plants and how they trap and digest their insect prey.
Includes index.
Includes glossary.
Includes bibliography.
4-8
Keywords: Venus's flytrap; Waterwheel plant; Carnivorous plants